Diversification of Banks' International Portfolios: Evidence and Policy Lessons - Claudia M. Buch; Katja Neugebauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Over the past decades, banks have significantly increased their cross-border asset positions. The ongoing crisis on international financial markets has raised the question whether this increase in cross-border activities has allowed banks to diversify risks and to what extent it has increased banks' exposure to systemic risks. In this contribution, we review the existing empirical evidence.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: F3; 330; international banking; financial integration